Implementasi Software Akuntansi Dalam Upaya Meningkatkan Kinerja Pelaporan Keuangan: (Studi Kasus CV. Agro Karya Utama) - Renaldy Septianto; Haninun Haninun (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This study aims to make proper and accurate planning in using accounting software. The method used in this research is qualitative. The location of the research was carried out at CV. Main Work Agro. The selected data collection techniques were observation, interviews, and documentation and then the data were analyzed using data displays, data reduction, and conclusions. The results of this study indicate that the obstacle experienced in applying accounting application software is age. Then, the efforts made to improve the performance of financial reporting through accounting application software are to bring in mentors who are experts in their fields as assistants in understanding staff who are in financial positions. In addition, the effect of applying this accounting application software is very significant on the performance of the CV factory financial reporting. Main Work Agro. This is because the application of this accounting software is a big variation in improving the performance of factory financial reporting.